(untitled) (Research, Society and Development, 2022)
Inbreeding depression as a consequence of mating between related animals, driven by reproductive biotechnologies and selection methods, affects traits of zootechnical interest, which causes economic and genetic diversity losses, in addition to limiting genetic progress. This review article exposes, through narrative review, causes and effects of inbreeding depression, with special attention to inbreeding coefficient estimates. From classical inbreeding coefficient calculated by pedigree to modern methodologies that indicate real levels of allele sharing, such as matrices of genomic relationships and homozygous races (ROH) are presented. The impact of inbreeding depression on traits related to production, health, fertility, and conformation is discussed in the context of different Holstein populations. It is concluded that much is known about inbreeding depression in Holstein populations; however, with the advent of genomics, and with it new approaches, the understanding of inbreeding depression can be expanded.